A randomised, multi-center, open trial comparing a semi-automated closed vitrification system with a manual open system in women undergoing IVF. Issue 8 (15th June 2021) - Hajek, Jennifer; Baron, Rebecca; Sandi-Monroy, Nathallie; Schansker, Stefanie; Schoepper, Beate; Depenbusch, Marion; Schultze-Mosgau, Askan; Neumann, Kay; Gagsteiger, Friedrich; von Otte, Soeren; Griesinger, Georg
Abstract: STUDY QUESTION: What are outcome and procedural differences when using the semi-automated closed Gavi ® device versus the manual open Cryotop ® method for vitrification of pronuclear (2PN) stage oocytes within an IVF program? SUMMARY ANSWER: A semi-automated closed vitrification method gives similar clinical results as compared to an exclusively manual, open system but higher procedure duration and less staff convenience. WHAT IS KNOWN ALREADY: A semi-automated closed vitrification device has been introduced to the market, however, little evaluation of its performance in a clinical setting has been conducted so far. STUDY DESIGN, SIZE, DURATION: This prospective, randomised, open non-inferiority trial was conducted at three German IVF centers (10/2017–12/2018). Randomization was performed on day of fertilization check, stratified by center and by indication for vitrification (surplus 2PN oocytes in the context of a fresh embryo transfer (ET) cycle or 'freeze-all' of 2PN oocytes). PARTICIPANT/MATERIAL, SETTING, METHODS: The study population included subfertile women, aged 18–40 years, undergoing IVF or ICSI treatment after ovarian stimulation, with 2PN oocytes available for vitrification. The primary outcome was survival rate of 2PN oocytes at first warming procedure in a subsequent cycle and non-inferiority of 2PN survival was to be declared if the lower bound 95% CI of the mean difference in survival rate excluded a difference larger than 9.5%; secondary, descriptive outcomes included embryo development, pregnancy and live birth rate, procedure time and staff convenience. MAIN RESULTS AND THE ROLE OF CHANCE: The randomised patient population consisted of 149 patients, and the per-protocol population (patients with warming of 2PN oocytes for culture and planned ET) was 118 patients. The survival rate was 94.0% (±13.5) and 96.7% (±9.7) in the Gavi ® and the Cryotop ® group (weighted mean difference −1.6%, 95% CI −4.7 to 1.4, P  = 0.28), respectively, indicating non-inferiority of the Gavi ® vitrification/warming method for the primary outcome. Embryo development and the proportion of top-quality embryos was similar in the two groups, as were the pregnancy and live birth rate. Mean total procedure duration (vitrification and warming) was higher in the Gavi ® group (81 ± 39 min vs 47 ± 15 min, mean difference 34 min, 95% CI 19 to 48). Staff convenience assessed by eight operators in a questionnaire was lower for the Gavi ® system. The majority of respondents preferred the Cryotop ® method because of practicality issues. LIMITATIONS, REASON FOR CAUTION: The study was performed in centers with long experience of manual vitrification, and the relative performance of the Gavi ® system as well as the staff convenience may be higher in settings with less experience in the manual procedure. Financial costs of the two procedures were not measured along the trial. WIDER IMPLICATIONS OF THE FINDINGS: With increasing requirements for standardization of procedures and tissue safety, a semi-automated closed vitrification method may constitute a suitable alternative technology to the established manual open vitrification method given the equivalent clinical outcomes demonstrated herein. STUDY FUNDING/COMPETING INTERESTS: The trial received no direct financial funding. The Gavi ® instrument, Gavi ® consumables and staff training were provided for free by the distributor (Merck, Darmstadt, Germany) during the study period. The manufacturer of the Gavi ® instrument had no influence on study protocol, study conduct, data analysis, data interpretation or manuscript writing. J.H. has received honoraria and/or non-financial support from Ferring, Merck and Origio. G.G. has received honoraria and/or non-financial support from Abbott, Ferring, Finox, Gedeon Richter, Guerbet, Merck, MSD, ObsEva, PregLem, ReprodWissen GmbH and Theramex. The remaining authors have no competing interests. TRIAL REGISTRATION NUMBER: ClinicalTrials.gov NCT03287479. TRIAL REGISTRATION DATE: 19 September 2017. DATE OF FIRST PATIENT'S ENROLMENT: 10 October 2017.